Representasi Gender dalam Media Sosial TikTok: Kajian Semiotika Visual Sosial Theo van Leeuwen dan Gunther Kress - Wulan Fadillah; Juanda Juanda*; Nensilianti Nensilianti (Universitas Suryakancana, 2026)
This article will describe forms of gender representation in TikTok video content based on Theo van Leeuwen and Gunther Kress's theory of Social Visual Semiotics. The research was conducted using a descriptive qualitative approach with an analysis of three visual metafunctions: representational meaning, interactional meaning, and compositional meaning. Data were obtained through documentation techniques and non-participant observation of gender-themed TikTok content. The results show that TikTok is a multimodal space that displays various forms of gender representation, ranging from the reinforcement of traditional stereotypes to resistance to gender role constraints. Multimodal elements such as visuals, text, audio, gestures, camera angles, and lighting work simultaneously to shape social meaning. TikTok thus functions as an ideological arena that helps build public awareness of gender equality.Keywords: multimodality; gender representation; social visual semiotics; TikTokArtikel ini akan mendeskripsikan bentuk representasi gender dalam konten video TikTok berdasarkan teori Semiotika Visual Sosial Theo van Leeuwen dan Gunther Kress. Penelitian dilakukan menggunakan pendekatan kualitatif deskriptif dengan analisis tiga metafungsi visual, yaitu representational meaning, interactional meaning, dan compositional meaning. Data diperoleh melalui teknik dokumentasi dan observasi nonpartisipan terhadap konten TikTok bertema gender. Hasil penelitian menunjukkan bahwa TikTok menjadi ruang multimodal yang menampilkan beragam bentuk representasi gender, mulai dari penguatan stereotip tradisional hingga resistensi terhadap batasan peran gender. Elemen multimodal seperti visual, teks, audio, gestur, sudut pandang kamera, dan pencahayaan bekerja secara simultan membentuk makna sosial. TikTok dengan demikian berfungsi sebagai arena ideologis yang turut membangun kesadaran masyarakat terhadap kesetaraan gender.Kata kunci: multimodalitas; representasi gender; semiotika visual sosial; TikTok